As estruturas silábicas e a redução vocálica no Português Europeu (Revista de Estudos da Linguagem, 2003)
This paper discusses vowel behavior in relation to syllable structurein European Portuguese. The analysis is based on GovernmentPhonology (Kaye, Lowenstamm and Vergnaud, 1985, 1990).We will argue that syllabic constituents in European Portuguesedetermine, to a great extent, vowel behavior. Branching nucleiand rhymes are the structures which most clearly determine thevalue of vowels in unstressed positions. As we will see throughoutthis paper, vowel reduction is clearly conditioned by syllablestructures.